Polietilen Mencegah Hipotermia Neonatus Prematur pada Proses Transportasi di Rumah Sakit - Titik Ambar Asmarini; Yeni Rustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine whether polyethylene is effective in preventing preterm neonatal hypothermia during the transportation process in the hospital. This research method is a systematic literature review from four databases and eight research studies selected according to inclusion and exclusion. The results showed that polyethylene effectively prevented hypothermia in the transport process and was also used in preterm birth and peripheral vein insertion. In conclusion, polyethylene is more effective and safer to prevent hypothermia, control temperature regulation quickly, and improve oxygen saturation, but it is at risk of causing hyperthermia. Keywords: Hypothermia, Neonates, Plastics, Polyethylene, Transportation